Organic Wheat Selection Through GGE Biplot Analysis - Bayhan, Merve; YILDIRIM, Mehmet (ISPEC Journal of Agricultural Sciences, 2021)
The aim of this study is to determine the performances of bread wheat genotypes under organic and conventional conditions. In addition, suitable genotypes for organic conditions determines by GGE biplot analysis. The study was carried out in the research and application area of Dicle University Faculty of Agriculture in Diyarbakır in rainy conditions during the 2019-2020 production season. In this study, materials were used as follows: 27 bread wheat genotypes from local cultivars and 3 check cultivars (Empire, Pehlivan and Ceyhan-99). Genotype adaptation and stability were evaluated by GGE biplot analysis on the basis of grain yield and quality characteristics (protein ratio and wet gluten). Genotypes have shown different performances in different environments. While genotype number 8 showed the best performance in organic conditions both in terms of yield and quality characteristics, genotypes numbered 19 and 22 had the highest values ​​in terms of yield and quality characteristics in conventional conditions. Genotype numbered 19 in terms of grain yield and genotypes numbered 2, 7 and 12 in terms of quality characteristics are the most ideal genotypes due to their high yield means and stability. These genotypes can be used directly as parents in organic production or in breeding programs for the development of new wheat varieties.